Analysis of Thorium Pin Cell Burnup of the PWR using WIMS Code - Panggabean, Jonny Haratua; Rajagukguk, Santo Paulus; Bakhri, Syaiful (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2022)
A thorium-fueled benchmark comparison was made in this study between state-of-the-art codes, WIMSD-5B code to MOCUP (MCNP4B + ORIGEN2), and CASMO-4 for burnup calculations as an effort to examine the possible benefits of using thorium in PWR fuel. WIMSD-5B calculations employ the same model as a reference, while for MOCUP and CASMO, there are some differences in methodology and cross-section libraries. On a PWR pin cell model, eigenvalue and isotope concentrations were examined up to high burn-up. The eigenvalue comparison as a function of burn-up is in good agreement, with a maximum difference of less than 5% and an average absolute difference of less than 1%. The isotope concentration comparisons outperform a set of ThO2-UO2 fuel benchmarks and are comparable to a set of uranium fuel benchmarks previously published in the literature. As a burn-up function, the eigenvalue comparison is discussed in this paper. The actinide and fission product data sources for a typical thorium fuel are reported in the WIMSD-5B burnup calculations. The reasons for discrepancies in coding are examined and explored.